Addressing Halal Industry Sustainability Through Halal Certification Bodies and IR.4.0 Techonology - Adlin Masood; Alina Abdul Rahim (Universiti Sains Islam Malaysia, 2024)
3rd INTERNATIONAL HALAL MANAGEMENT CONFERENCE (3rd IHMC 2021) “Sustainability and Empowerment of Halal Industry in The Midst of COVID19-Pandemic” Date: 23rd – 24th August 2021, Malaysia eISBN: 978-967-440-956-2 Organised by : Faculty of Economy and Muamalat, USIM